Numerical Simulation Of The Cascade Aerator System For The Removal Of Iron And Manganese - Jamil, Rhahimi (2019)
In groundwater treatment, many techniques have been investigated, including the cascade aerator system, which is a technique to eliminate heavy metals such as iron and manganese. The cascade aerator is also used as an effective, low-cost method to treat groundwater. In this study, the Lattice Boltzmann Method (LBM) was used to investigate the aeration process in a newly-designed cascade aerator model. For this new cascade aerator, different dimensions were used to determine the best design that could reduce the concentration of iron and manganese. Two sets of LBM simulations, and two sets of Particle Image Velocimetry (PIV) experiments were carried out, and the velocity of the flow were calculated. Based on the findings, it was shown that the LBM simulations, and PIV data were in good agreement with each other in terms of velocity distribution. In addition, it was also found that water velocity had a significant influence on aeration efficiency. Cavitation damaged the overflow structure of the surge, and the oxidation process reduced the iron and manganese in the water by increasing the dissolved oxygen. In this study, two physical models of a cascade aerator were used, Model A and Model B, with flow rates of 1.78 l/h, 2.0 l/h, and 2.20 l/h. The dissolved oxygen concentration was increased from 0.8 to 1.4 mg/L for Model A, and from 0.7 to 1.2 mg/L for Model B. The removal of iron and manganese was increased from 11.3 mg/L up to 16.3 mg/l (2%), and 0.31 mg/L up to 0.50 mg/l (21%) respectively. For a more comprehensive comparison, Model C was explored using LBM simulations. The length of the steps in Model C was longer than Model A and Model B. The rest of the dimensions in Model C were similar to the other two models. Overall, the length of the Model C was 400 mm. A significant increase could be observed from the removal percentages recorded by Model C, which were 50% to 52% higher than those recorded in Model A, and 55% to 63% higher than Model B. These models were designed using Computational Fluid Dynamics (CFD) for numerical simulation. The CFD analysis allowed for the prediction of the presence of iron and manganese in the cascade aeration model. Simulations of iron and manganese particles were performed using the Dispersed Phase Method (DPM). Results obtained on the presence of iron (10%) and manganese (5%) were computed from the simulation. The results on the presence of iron and manganese was almost identical to the actual experimental work. Therefore, CFD was used successfully as a tool for design, and prediction of the presence of particles in the cascade aerator. In addition, with the use of the Avogadro Software, the interactions between the visible particles, and geometric optimisation readings were obtained based on the results on the reactions between water, iron, and manganese. This showed that the use of the Avogadro Software can help in observing the reactions between water, iron, and manganese particles. This can be seen with each addition of particles showing an increase in the removal of iron and manganese in groundwater.